The Atlantic monthly (Atlantic Monthly Group, 1993)
A general interest magazine covering a broad range of topics including politics, society, the arts, and culture. Contains some articles and reviews originally issued in the print version of Atlantic Monthly, as well as material issued exclusively for the online version.